Tantangan Strategi Tobacco Harm Reduction (THR) dalam Pembatasan Rokok Elektrik oleh Kaum Remaja - Nurul Hikmah Baharuddin; Andi Sani; Firman Firman; Nurhidayati Islamiah (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Tobacco control policies are one of the concerns in a series of sustainable development goals. In terms of reducing exposure to cigarette smoke or for smokers who cannot stop using tobacco products containing nicotine, electronic cigarettes or vapes are said to be a safer alternative to conventional cigarettes by prioritizing the concept of a "tobacco harm reduction" strategy. The highest use of e-cigarettes is among teenagers with the vulnerable group aged 10-14 years at 10.6%. This research aimed to determine the challenges of tobacco harm reduction strategies in limiting e-cigarettes for teenagers. This research was a quantitative study with a cross-sectional design, involving 98 teenagers aged 10-24 years with simple random sampling as the selection method. Data was collected through questionnaires and analyzed using linear regression tests. The results of the study found that the vulnerability and seriousness felt by teenagers in using e-cigarettes together influenced the implementation of tobacco harm reduction, with p-value of 0.000. It was concluded that the application of the tobacco harm reduction concept would be more effective if e-cigarettes could pose a much smaller risk than tobacco cigarettes. Commitment is required for e-cigarette users as a form of action to initiate smoking cessation.Keywords: tobacco harm reduction; teenager; vulnerability; seriousness ABSTRAK Kebijakan tentang pengendalian tembakau menjadi salah satu perhatian dalam serangkaian tujuan pembangunan berkelanjutan. Dalam hal mengurangi paparan asap rokok atau bagi perokok yang tidak dapat berhenti menggunakan produk tembakau yang mengandung nikotin, rokok elektrik atau vape disebut sebagai salah satu alternatif yang lebih aman daripada rokok konvensional dengan mengedepankan konsep strategi “tobacco harm reduction”. Penggunaan rokok elektrik terbanyak terdapat pada kalangan remaja dengan kelompok rentan berusia 10-14 tahun sebesar 10,6%. Penelitian ini bertujuan untuk menentukan tantangan strategi tobacco harm reduction dalam pembatasan rokok elektrik bagi kaum remaja. Penelitian ini merupakan penelitian kuantitatif dengan rancangan cross-sectional, yang melibatkan 98 remaja berusia 10-24 tahun dengan simple random sampling sebagai metode pemilihan. Data dikumpulkan melalui kuesioner dan dianalisis menggunakan uji regresi linear.  Hasil penelitian menemukan bahwa kerentanan dan keseriusan yang dirasakan remaja dalam penggunaan rokok elektrik secara bersama-sama berpengaruh terhadap penerapan tobacco harm reduction, dengan nilai p = 0,000. Disimpulkan bahwa penerapan konsep tobacco harm reduction akan lebih efektif jika rokok elektrik dapat menimbulkan risiko yang jauh lebih kecil daripada rokok tembakau. Komitmen diperlukan bagi pengguna rokok elektrik sebagai bentuk tindakan memulai berhenti merokok.Kata kunci: tobacco harm reduction; remaja; kerentanan; keseriusan